WILLINGNESS TO SPEAK: WHAT FACTORS INFLUENCE EFL LEARNERS? - Nyimas Triyana; Habizar Habizar; Melda Nifia Putri (English Review: Journal of English Education, 2023)
The online learning mode has dramatically altered the manner of the way how communication is conducted in learning at higher education or schools for the past two years. It has led to a considerable change in how learning is carried out, transferring it from an offline to an online setting that permits long distance connection and communication. However, this has an effect on students’ engagement in class as many of them exhibit passive or unresponsive behavior in participating the online learning sessions. This qualitative study aims to explore the influencing factors affect students' willingness to participate in zoom sessions during online classes at English Department, Universitas Jambi. The data was gathered through the online classroom observations and interviews with the six EFL learners, and the data was then analyzed based on the theoretical built-themes of Willingness to Communicate (WTC). The finding reveals that 1) The demotivating factors influence EFL learners’ willingness to speak in zoom class were derived by the situational factor such as difficult task types and models, the unfamiliar topic of class discussion, the lecturers’ personal characteristics, the inconvenienced time or schedule of the class meeting and a trouble Internet connection. While 2) The depressing factors influenced by the psychological component, were comprised by the lack of self-confidence, low level of English language proficiency, L2 learning anxiety and students’ individual personality.